Alfvén cascade eigenmodes above the TAE-frequency and localization of Alfvén modes in D–3He plasmas on JET. (1st May 2022) - Dreval, M.; Sharapov, S.E.; Kazakov, Ye.O.; Ongena, J.; Nocente, M.; Calado, R.; Coelho, R.; Ferreira, J.; Figueiredo, A.; Fitzgerald, M.; Garcia, J.; Giroud, C.; et al.
Abstract: Various types of Alfvén eigenmodes (AEs) have been destabilized by fast ions over a broad frequency range from ∼80 kHz to ∼700 kHz in a series of JET experiments in mixed D– 3 He plasmas heated with the three-ion ICRF scenario (2020 Nocente et al Nucl. Fusion 60 124006). In this paper, we identify the radial localization of AEs using an X-mode reflectometer, a multiline interferometer and soft x-ray diagnostics. The analysis is focused on the most representative example of these measurements in JET pulse #95691, where two different types of Alfvén cascade (AC) eigenmodes were observed. These modes originate from the presence of a local minimum of the safety factor q min . In addition to ACs with frequencies below the frequency of toroidal Alfvén eigenmodes (TAEs), ACs with frequencies above the TAE frequency were destabilized by energetic ions. Both low- ( f ≈ 80–180 kHz) and high-frequency ( f ≈ 330–450 kHz) ACs were localized in the central regions of the plasma. The characteristics of the high-frequency ACs are investigated in detail numerically using HELENA, CSCAS and MISHKA codes. The resonant conditions for the mode excitation are found to be determined by passing ions of rather high energy of several hundred keV and similar to those established in JT-60U with negative-ion-based NBI (2005 Takechi et al Phys. Plasmas 12 082509). The computed radial mode structure is found to be consistent with the experimental measurements. In contrast to low-frequency ACs observed most often, the frequency of the high-frequency ACs decreases with time as the value of q min decreases. This feature is in a qualitative agreement with the analytical model of the high-frequency ACs in Breizman et al (2003 Phys. Plasmas 10 3649). The high-frequency AC could be highly relevant for future ITER and fusion reactor plasmas dominated by ∼MeV energetic ions, including a significant population of passing fast ions.